P293 Is Obstructive Sleep Apnoea A Risk Factor For Chronic Kidney Disease?. (10th November 2014) - Rauf, F; Kerks, J; Comer, D; Dasgupta, I; Daniels, M; Mukherjee, R; Wharton, S
Abstract : Background: Obstructive sleep apnoea (OSA) is associated with intermittent hypoxaemia which leads to activation of a number of pathways including oxidative stress, sympathetic nervous system, endothelial dysfunction and inflammation. These in turn lead to hypertension and atherosclerosis. There is some evidence that the same process may predispose to renal dysfunction. In this retrospective study, we compared a group people with hypertension and OSA on continuous positive airways pressure therapy (CPAP) with matched control group not known to have OSA. Method: Patients with known OSA and controls matched for age, sex and BMI were selected retrospectively from a hypertension clinic database. The two groups were compared using the following parameters: mean 24-hour systolic blood pressure (SBP, mmHg), mean serum creatinine (micromol/l) and mean urine albumin/creatinine ratio (ACR. mg/mmol). Results: Forty-nine patients were identified with confirmed OSA on CPAP. 6 were excluded due to insufficient data. Of the 43 remaining patients 35 were male, the mean age was 53.5 years and the mean BMI was 34.6 km/m 2 . The mean SBP was 143 in patients versus 135 in controls (p = 0.04). The mean serum creatinine was 94.0 in patients versus 93.4 in controls (p = 0.45). The mean ACR was 2.50 in patients versus 0.63 in controls (p = 0.031). Conclusion: This retrospective case-control study shows a higher prevalence of hypertension and proteinuria in patients with treated OSA when compared with controls matched for age, sex and BMI. OSA in the patients may not have been adequately treated. There may have been undiagnosed OSA in the controls. Patients' higher proteinuria may have been caused by their more severe hypertension. Causation is not proven. However this study raises the possibility that OSA might predispose to chronic kidney disease. A larger, prospective study might confirm this finding and provide information on causation.